Penerapan Teknik Rendam Kaki Air Hangat dan Teknik Relaksasi Otot Progresif pada Pasien Hipertensi - Surya Apriani Silaban; Sri Indaryati; Lilik Pranata (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension is a non-communicable disease that can lead to cardiovascular complications and requires both pharmacological and non-pharmacological management. One of the non-pharmacological therapies that can be applied is warm water foot soaking and progressive muscle relaxation, which may help reduce blood pressure through peripheral vasodilation, stimulation of the parasympathetic nervous system, and decreased sympathetic nervous system activity. This study aimed to analyze the implementation of nursing care through warm water foot soaking therapy and progressive muscle relaxation to reduce blood pressure in patients with hypertension. The method used was a case study with a pre-experimental design using a one group pre-test post-testapproach involving three hypertensive patients, with the intervention administered once daily for three days. The results showed a decrease in blood pressure in all patients. The average systolic reduction was 5.3 mmHg, 12.3 mmHg, and 5.6 mmHg, while the diastolic reduction was 1.6 mmHg, 2.6 mmHg, and 4 mmHg, respectively. In addition, all patients reported a reduction in pain scale. It can be concluded that warm water foot soaking therapy combined with progressive muscle relaxation is effective as a complementary nursing intervention to help reduce blood pressure in patients with hypertension.